A day in the life of Marlon Bundo - Bundo, Marlon; Twiss, Jill 1976- (Chronicle Books, 2018)
When Vice President Mike Pence's pet rabbit Marlon Bundo and another male bunny fall in love and decide to get married, they encounter opposition from a rule-making stink bug until their animal friends, who embrace individuality, decide to vote on the issue